a PEMBERDAYAAN KUALITAS USAHA MELALUI INOVASI DIGITALY UMKM: PEMBERDAYAAN KUALITAS USAHA MELALUI INOVASI DIGITALY UMKM - Windayanti, Windayanti; Febrian, Wenny Desty Febrian (Andhara, 2024)
A person's success can be started from the education that is in his family, because that's where the child begins to know the world. Individuals who want to be advanced in their business of course he can also become a successful entrepreneur. Who will not only depend on themselves but can at least pay for themselves and their families. Therefore, an MSME actor must be technology literate and see what opportunities can be explored and utilized to open a business that can generate money. The location of PKM partners is in the Dian Nusantara University area. The partners served are located in the Tanjung Duren area which is a densely populated area that is integrated between residents' settlements, markets, schools. This area is strategic because it is traversed by public transportation so that it is automatically easily accessible by many people. The activities carried out before carrying out community service, namely conducting library research on materials related to entrepreneurship, preparing materials and supporting tools for entrepreneurial seminars, conducting trials of material designs to be delivered, determining the implementation time and duration. community service activities together with the implementing team, Sending participants' willingness letters regarding their willingness to attend seminars, and Receiving enthusiastic responses from participants for their willingness to carry out community service activities. Keywords: Empowerment, Business Quality, Innovation, Digitization